The dynamics of a parametrically driven damped pendulum - Das, Alaka; Kumar, Krishna (Zielona Góra: Uniwersytet Zielonogórski)
Ordered and chaotic states of a parametrically driven planar pendulum with viscous damping are numerically investigated. The damping makes the number of chaotic windows fewer but with larger width. Stroboscopic maps of the chaotic motion of the pendulum, driven either subharmonically or harmonically, show strange attractors with inversion symmetry in the phase plane.
Keywords: parametric vibration; Floquet analysis; Lyapunov exponents; stroboscopic maps; chaos